Effects of the hardness and roughness on the plastic deformation properties of electroplated gold bumps during thermocompression bonding. (November 2022) - Elsotohy, M.; Froehlich, J.; Dietrich, L.; Oppermann, H.; Schneider-Ramelow, M.
Abstract: Within the scope of this work, an optimization approach of existing investigations on electroplated hard gold contacts is to be developed, which have an initial Vickers hardness of 103 HV. These investigations envisage the height-controlled bonding of structures in the multichip integration of optical components. The investigations relate to the influence of material hardness and roughness on the plastic deformation behaviour during bond formation by thermocompression bonding (TCB). Furthermore, pre-treatments such as mechanical surface planarization and chemical surface activation using atmospheric pressure plasma are employed prior to the bonding process to enable the reduction of the bonding parameters pressure and temperature and consequently contribute to control the plastic deformation during thermocompression and reduce the typical plastic deformation range of 30 % to a deformation range below 5 %. The previous investigations were performed on gold contacts, which have been thermally annealed prior to the bonding process and resulted in a plastic deformation range up to 30 %. With the new approach, i.e. throughout the material hardening and altering the surface condition, a plastic deformation range below 3 % was successfully obtained. The attainable bonding temperatures and bonding pressures were between 190 °C–250 °C and 145 MPa–230 MPa, respectively. The bonding time varied between 30 s and 60 s. Highlights: Height-controlled bonding of gold structures is a critical aspect in the multichip integration of optical components Thermocompression bonding approach aiming towards reproducible plastic deformation of hard gold contacts A Reduction of the thermocompression stress to 0 % by controling the hardness, roughness as well as the surface cleanliness